2014
DOI: 10.3368/jhr.49.4.906
|View full text |Cite
|
Sign up to set email alerts
|

Ability, Parental Valuation of Education, and the High School Dropout Decision

Abstract: We use a large, rich Canadian micro-level dataset to examine the channels through which family socio-economic status and unobservable characteristics affect children's decisions to drop out of high school. First, we document the strength of observable socio-economic factors: our data suggest that teenage boys with two parents who are themselves high school dropouts have a 16% chance of dropping out, compared to a dropout rate of less than 1% for boys whose parents both have a university degree. We examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 6 publications
1
40
2
1
Order By: Relevance
“…16 Specifically, as described in further detail in the Estimation subsection 3,4 below, we use the result of Ferguson (1983) that a mixture of normal distributions can approximate any distribution. For each of the three competencies, we assume that the given competency is a mixture of two Normal distributions and estimate the standard deviation of each distribution 15 Our measurement equations differ sharply from Foley et al (2014) and Foley (forthcoming) who are just identified, and we overlap with using the PISA reading score, parental question on highest educational attainment and question on the child's perspective of the amount of education their parent hopes they complete. While Foley et al (2014) and Foley (forthcoming) allow for more correlations between the factors across the measurement equation, this relaxation comes at the cost of imposing additional strong covariance restrictions between the residuals in the system of measurement equations for identification.…”
Section: Latent Competenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Specifically, as described in further detail in the Estimation subsection 3,4 below, we use the result of Ferguson (1983) that a mixture of normal distributions can approximate any distribution. For each of the three competencies, we assume that the given competency is a mixture of two Normal distributions and estimate the standard deviation of each distribution 15 Our measurement equations differ sharply from Foley et al (2014) and Foley (forthcoming) who are just identified, and we overlap with using the PISA reading score, parental question on highest educational attainment and question on the child's perspective of the amount of education their parent hopes they complete. While Foley et al (2014) and Foley (forthcoming) allow for more correlations between the factors across the measurement equation, this relaxation comes at the cost of imposing additional strong covariance restrictions between the residuals in the system of measurement equations for identification.…”
Section: Latent Competenciesmentioning
confidence: 99%
“…For each of the three competencies, we assume that the given competency is a mixture of two Normal distributions and estimate the standard deviation of each distribution 15 Our measurement equations differ sharply from Foley et al (2014) and Foley (forthcoming) who are just identified, and we overlap with using the PISA reading score, parental question on highest educational attainment and question on the child's perspective of the amount of education their parent hopes they complete. While Foley et al (2014) and Foley (forthcoming) allow for more correlations between the factors across the measurement equation, this relaxation comes at the cost of imposing additional strong covariance restrictions between the residuals in the system of measurement equations for identification. For completeness, the variables used as outcomes in the measurement equation system that differ from our own study include self-reported high school GPA, parental savings for child education, and responses to different questions related to effort spent on homework for non-cognitive skills.…”
Section: Latent Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way wealth can affect the optimal policy of students is by introducing credit constraints. In my model, students do not face a credit constraint motivated by the evidence in Heckman, Lochner, and Taber (1998), Cameron and Heckman (2001), Keane and Wolpin (2001), Cameron and Taber (2004), Foley, Gallipoli, andGreen (2009), andNielsen, Sorensen, andTaber (2010), which find no (or little) effect of credit constraints in shaping postsecondary enrollment, and Stinebrickner and Stinebrickner (2008), which finds no effect of credit constraints in explaining dropout behavior. 8 In the end, the combination of exponential utility function and no credit constraints simplifies the model considerably.…”
Section: Assumption 1 the Ratio Of Densitiesmentioning
confidence: 99%
“…Further, Belley et al (2009) show that the impact of parental income on high school completion is lower in Canada than in the US. A recent paper by Foley et al (2009) finds that the socioeconomic gradient of high school dropout propensity in Canada is considerably reduced when controlling for cognitive ability at age 15. In particular, adding a measure of parents value placed on education effectively removes the direct impact of parental education on high school completion.…”
Section: Introductionmentioning
confidence: 99%